Application of dihaploid breeding technology in variety development and QTL mapping in rice (Oryza sativa L.) - Lapitan, Victoria C. (Transactions of the National Academy of Science and Technology, 2011)
Dihaploid technology has become a promising tool in breeding for producing homozygous lines more rapidly than most conventional breeding methods. Doubled haploids (DH) are also excellent materials for genetic studies because of their homozygosity and uniformity. A total of 313 DHS were generated thru another culture from the Fl of PSB Rc10 and Nipponbare. Characterization of these DHs revealed the very high homogeneity and stability at the DNA level using SSR analysis and under field conditions. Field trials of 237 DHs in 2009 WS resulted in selection and advancement of 54 superior lines in 2010 DS and WS. Ten 10 DHS on been selected as promising lines based on high yield, phenotypic accepta tolerance to major pests, and uniformity which are better compara the checks: PSB Rc10. PSB Rc18. and PSB Rc82. In less than elite breeding lines were developed while conventionally, it takes for selected inbreds to reach yield trial. Stable and potential donor parentals were also developed and included in the germplasm pool based to blast (9), early maturity (3), enhanced grain quality medium plant height (10). On the other hand, a mapping consisting of 219 DHs was used for identifying QTL for grain quality traits using 205 SSR markers. Thirteen QTLs were identified; three content and five each for gel consistency and gelatinization QTL mapping for drought tolerant traits such as days to ma fertility, early vigor, and green leaf retention is now ongoing us mapping population. Information on mapped OTLs associated with these traits and the SSR markers that have tight linkage to them may be used to speed up the process of breeding new rice varieties with better quality and drought tolerance through molecular marker-assisted selection (MAS).